Sex Determination Using Mandibular Ramus Flexure Width On Left Side In South Indian Population - A Short Study - Krishna B, Ashwin; Dinesh, Dinesh (Journal of Neonatal Surgery, 2024)
Introduction :Sex of an individual can be identified by bones eg with all the bones we can identify the sex by 100%. Mandible is considered as one of the stronger bones of the skull available for gender identification. Mandibular measurements can be used for the identification of gender either on dry mandible or through panoramic radiography or cone-beam computed tomography Aim: The purpose of our study is to assess the usefulness of mandibular ramus flexure (left) in gender determination. Materials and methods: An orthopantomograph was used in a retrospective study of 60 subjects (30 males and 30 females). They ranged in age from 20 to 40 years. For the study, ideal orthopantomography was chosen. These samples were separated based on their birth date and the date of the radiograph. Results: The ramus flexure of males were 2.93 and the ramus flexure of females were 2.67. The standard deviation of males was 0.73968 and females were 0.66089. The difference between males and females was 0.07879. The standard mean error of males was 0.13505 and females was 0.12066. The difference in standard mean error was 0.01439. Conclusion: We discovered that orthopantomograph measurements of the mandibular ramus flexure (left side) were reliable for determining sex. As a result, we strongly advise using mandibular ramus flexure (left side) as a forensic aid for gender determination...